Gotta go! Gotta go! - Swope, Sam.; Riddle, Sue, 1966- (New York : Farrar, Straus and Giroux, 2000)
Although she does not know why or how, a small creepy-crawly bug is certain that she must make her way to Mexico.
Keywords: Monarch butterfly -- Fiction; Butterflies -- Fiction; Caterpillars -- Fiction